Representing science: the theatre as a way of communicating culture. Educational effectiveness of the theatrical workshop with historical-scientific content - Vinci, Viviana (Formazione & insegnamento, 2015)
The crisis of scientific education has long been a central theme in political and cultural debates, both in the national and in the European field. This paper focuses on shaping educational and pedagogical potential for a new tool of scientific transmission, that starts from the experience and evaluation of a project spreading scientific knowledge in the school: theatre workshop. The inprogress inquiry protocol is made up of several methodological tools (i.e. interviews, questionnaires and video-recording analysis) and is placed on a descriptive and “bottom-up” perspective.